(untitled) (KYAMC Journal, 2017)
Original Article- Dual bronchodilation with QVA149 reduces patient-reported dyspnoea in COPD: BLAZE study (Ref: ERJ Express. Published on October 31, 2013 as doi: 10.1183/09031936.00124013) Abstract: The effect of a dual bronchodilator (QVA149) was evaluated combining Indacaterol and Glycopyrronium, on direct patient-reported dyspnoea in moderate-to severe COPD. In this multicentre, blinded, double-dummy, three-period crossover study, once-daily QVA149 provided superior improvements in patientreported dyspnoea and lung function versus placebo and tiotropium. These benefits were associated with improvements in other symptoms and reduced use of rescue medication. KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 804-805